The Role of Emoji in Personal Chatting in Building Long Distance Romantic Relationships - Khofidul A , Muhammad; Nirwana, Irma Dewi; Santosa, Gibran Yoga; Ananda, Desta Seren; Junaedi, Arif Rahman; Putri, Venus Aurora; Nuriza, Aurelia Zahwa (Professorline, 2025)
This study examines the role of emojis in building personal communication in long-distance romantic relationships. In the digital era, emojis have evolved from mere message decorations to important elements in digital communication, especially in the context of long-distance romantic relationships. Using a quantitative approach with an explanatory research type, this study involved 100 student respondents from various universities who were in long-distance relationships. Data collection was carried out through structured questionnaires, in-depth interviews, and digital conversation analysis. The results showed a strong positive correlation (r = 0.72) between emoji use and improved communication quality, with 78% of respondents consistently using emojis in their daily conversations. Facial expression emojis dominated use (85%), followed by heart and love symbol emojis (72%). A total of 76% of respondents reported increased message clarity, 68% experienced a decrease in communication misunderstandings, and 82% felt an increase in the effectiveness of emotional communication. Digital literacy had a significant positive correlation (r = 0.64) with the effectiveness of emoji use. The main challenges identified included differences in emoji interpretation (45%), dependence on internet connection (38%), and difficulty expressing complex emotions (32%). This research makes a significant contribution to understanding the role of emojis as a non-verbal communication tool in long-distance romantic relationships and can be the basis for developing more effective communication strategies in the digital era.